Studi Pemutus Arus Searah Berbasis Hybrid untuk Transmisi Arus Searah - Zulfiana Safitri Majid (KOLONI, 2023)
In improving the electrical transmission system, a stable and reliable integration system is needed. Based on research, direct current transmission systems are believed to be more efficient in distributing electrical energy, especially over long distances between power plant and electricity consumers. When direct current transmission is applied, the direct current breaker system will also be more crucial. For this reason, in this research, a more in-depth study was carried out regarding a hybrid-based direct current breaker system which can cut off the fault current very quickly for about 250µs and reduce commutation losses from semiconductor components. Keywords: DC Hybrid Circuit Breaker, High Voltage Direct Current, Integration